2007
DOI: 10.2174/138920107780487465
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance in Childhood Acute Myeloid Leukemia

Abstract: Therapy results in childhood AML differ from those of ALL. The development of drug resistance is the limiting factor in the therapy of AML. Different problems of drug resistance in childhood AML, with emphasis to age and in comparison to adult AML are presented. In vitro and in vivo aspects are discussed, together with mechanisms of resistance to cytostatic drugs, focused on clinical relevance of cellular drug resistance profile and its prognostic value. Possibilities of modulation and circumvention of drug re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 98 publications
(143 reference statements)
0
19
0
1
Order By: Relevance
“…Evidence has shown that AML patients who achieved CR had longer OS than non-CR patients [1820], and chemo-resistance is the main reason for treatment failure in AML [2527]. Hence, factors affect IC 50 of cytarabine may also influence prognosis of AML.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that AML patients who achieved CR had longer OS than non-CR patients [1820], and chemo-resistance is the main reason for treatment failure in AML [2527]. Hence, factors affect IC 50 of cytarabine may also influence prognosis of AML.…”
Section: Discussionmentioning
confidence: 99%
“…7 The main reason for treatment failure among patients with AML is resistance to therapy. [8][9][10] In addition, treatment with cytarabine is associated with a number of adverse side effects including myelosuppression, infections, mucositis, neurotoxicity, and acute pulmonary syndrome. 11 Cytarabine requires activation through intracellular phosphorylation to araC-triphosphate (ara-CTP).…”
Section: Introductionmentioning
confidence: 99%
“…Cytarabine is an antimetabolite and the mainstay of treatment for acute myeloid leukemia (AML) [6]. In some AML patients, resistance to cytarabine is a major reason for treatment failure and in others, cytarabine is associated with several adverse side effects, including myelosuppression and neurotoxicity [15][19]. In a study by the Children's Oncology Group of pediatric patients with AML, patients with African ancestry had significantly worse survival compared with patients of exclusively European ancestry [20].…”
Section: Introductionmentioning
confidence: 99%